Geographic Information System-Based Approach and Analysis of Housing Mismatches in Searches during Housing Selection - Le, To Quyen; Doan, Le-Vinh-Lam (Buildings (Basel), 2024)
This study aimed to explore the spatial interaction between search flow and house price levels. It utilized migration flow data from 2011 and house price data from the same year in Greater Manchester, United Kingdom. The methodology included Chi-square tests and a series of visual maps to explore and visualize the relationship between current areas and search areas. The study examined five house price ranges with matches and mismatches between search patterns and current patterns and tried to illuminate the underlying causes. The research results could prove beneficial for policymakers and planners in discerning distinct migratory patterns and geographical regions, thereby facilitating the formulation of well-informed decisions.